An introduction to sociolinguistics - Wardhaugh, Ronald (Blackwell textbooks in linguistics, 2015)
Summary: "Fully updated to reflect the most recent scholarship in the field and revised to include many more pedagogical features, An Introduction to Sociolinguistics, 7th Edition builds on its foundation as the most preeminent textbook in sociolinguistics, updated for today's students. Significantly revised discussions throughout each of the book's four key parts reflect the state of the field today. Includes new chapters on Pragmatics, Discourse Analysis, and Sociolinguistics and Education. Incorporates innovative new perspectives drawn from linguistic anthropology. Provides an accessible history of the development of sociolinguistic thought and how this fast-moving field is integral to our lives. Includes numerous opportunities for students to engage with ideas presented in the text through a new glossary, new Explorations and end-of-chapter exercises, links, and key concepts. New companion website includes links and resources for students". --Publisher.